Effect of C-terminus amidation of Aβ39–42 fragment derived peptides as potential inhibitors of Aβ aggregation. Issue 45 (21st July 2020) - Kapadia, Akshay; Patel, Aesan; Sharma, Krishna K.; Maurya, Indresh Kumar; Singh, Varinder; Khullar, Madhu; Jain, Rahul
Abstract : Amidated C-terminal fragment, Aβ39–42 derived non-cytotoxic β-sheet breaker peptides exhibit excellent potency, enhanced bioavailability and improved proteolytic stability. Abstract : The C-terminus fragment (Val-Val-Ile-Ala) of amyloid-β is reported to inhibit the aggregation of the parent peptide. In an attempt to investigate the effect of sequential amino-acid scan and C-terminus amidation on the biological profile of the lead sequence, a series of tetrapeptides were synthesized using MW-SPPS. Peptide D-Phe-Val-Ile-Ala-NH2 (12c ) exhibited high protection against β-amyloid-mediated-neurotoxicity by inhibiting Aβ aggregation in the MTT cell viability and ThT-fluorescence assay. Circular dichroism studies illustrate the inability of Aβ42 to form β-sheet in the presence of 12c, further confirmed by the absence of Aβ42 fibrils in electron microscopy experiments. The peptide exhibits enhanced BBB permeation, no cytotoxicity along with prolonged proteolytic stability. In silico studies show that the peptide interacts with the key amino acids in Aβ, which potentiate its fibrillation, thereby arresting aggregation propensity. This structural class of designed scaffolds provides impetus towards the rational development of peptide-based-therapeutics for Alzheimer's disease (AD).